HARMONY OF UZBEK NATIONAL CLOTHING CULTURE AND MODERNITY - Ibaydullaev , Temur (Научно-просветительский журнал "Наставник", 2021)
The article deals with the peculiarities of the culture of Uzbek traditional national dress, as well as analyzed the problems that arise in the harmonization of modern clothing with Uzbek traditional national dress and proposals for their solution from a philosophical and cultural point of view